Tri Kaya Parisudha sebagai Pilar Etika Bisnis Terhadap Keberlanjutan UMKM dengan Pendekatan Eksplanatori - Ariasih, Made Putri; Suwastika, Agus Made Surya; Aditiya, Kadek Duwi; Mahendra, Komang; Abigail Emilia Putri, Ni Kadek; Agus Deva Arthamahendra, I Gede (Journal of Business and Economics Research (JBE), 2025)
MSMEs play an important role in the Indonesian economy, but amidst the rapid development of the industry, MSMEs still face various challenges from both internal and external factors. This article discusses how business ethics based on the Tri Kaya Parisudha philosophy is applied to the problem of gaps that occur in the application of business ethics by MSMEs. The purpose of this study is to examine how Tri Kaya Parisudha can be adopted as a more contextual approach to business ethics and relevant for MSMEs in Bali Province. This article uses an explanatory sequential mixed method approach. Through the analysis results, it was found that business ethics based on the Tri Kaya Parisudha philosophy including speech (Wacika), thoughts (Manacika), and actions (Kayika) have a positive and significant influence on MSMEs. Not only does it provide a positive influence, MSMEs are also encouraged to implement sustainability in their businesses. In the Balinese socio-cultural context, moral and ethical values ​​have been alive and embedded in the lives of the community through various local wisdom teachings. Through business ethics based on Tri Kaya Parisudha, it can be a superior strategy based on local culture without abandoning the cultural roots of the community, especially in Bali. Thus, the results of this study demonstrate an empirical contribution in integrating the local cultural values ​​of Tri Kaya Parisudha with modern business ethics practices to support the sustainability of MSMEs in Bali.